(untitled) (KULT_online, 2017)
Storibuk Pairundu: Tales and Legends from the Kewa (Southern Highlands, Papua New Guinea), collected by Alex Yapua Ari and edited by Holger Jebens sketches a unique combination of tales and legends narrated by the indigenous people. Given several previous fieldworks in Papua New Guinea, this book frames in its introductory remarks the past ethnographic and anthropologic efforts in analysing fairy tales. Additionally, this volume features some facsimiles of Alex’s handwriting. In order to make the stories more accessible to the reader, Jebens augments his work with a group of photographs that depict different aspects of the people of Pairundu, such as clothes, food, and cultivating.